2014
DOI: 10.1093/jhered/esu028
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Drift Linked to Heterogeneous Landscape and Ecological Specialization Drives Diversification in the Alpine Endemic Columbine Aquilegia thalictrifolia

Abstract: The European Alpine system is an extensive mountain range, whose heterogeneous landscape together with Quaternary climatic oscillations significantly affected organismal diversity and distribution in Europe. The model genus Aquilegia represents a textbook example of a rapid and recent radiation through the Northern hemisphere, with the majority of the European taxa occuring in the Alpine system. However, the processes governing genetic differentiation of the genus in this complex geographic area are still wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…Overall, we observe that the genetic variation level in the two endemic species is lower than for the other Arabidopsis species with wide distribution range and the same mating system (self-incompatibility). For comparison, the narrow endemic Aquilegia thalictrifolia, distributed in a few valleys of the Italian South-Eastern Alps, also displayed a higher average Hexp (0.68 ± 0.19), which is twice as high as for the two Arabidopsis endemics (Lega et al 2014). In A. cebennensis π, θw and Hexp were low and almost similar for the three subpopulations, and similar to what was estimated for the whole species.…”
Section: Genetic Diversitysupporting
confidence: 68%
“…Overall, we observe that the genetic variation level in the two endemic species is lower than for the other Arabidopsis species with wide distribution range and the same mating system (self-incompatibility). For comparison, the narrow endemic Aquilegia thalictrifolia, distributed in a few valleys of the Italian South-Eastern Alps, also displayed a higher average Hexp (0.68 ± 0.19), which is twice as high as for the two Arabidopsis endemics (Lega et al 2014). In A. cebennensis π, θw and Hexp were low and almost similar for the three subpopulations, and similar to what was estimated for the whole species.…”
Section: Genetic Diversitysupporting
confidence: 68%
“… Geng et al (2009) found short-distance genetic structure patterns related to limited gene dispersal along with substantial levels of gene flow and slow rates of genetic drift between topographically separated populations. Many other authors reported genetic structure at larger landscape scales (e.g., Aægisdóttir et al, 2009 ; Lega et al, 2014 ) related to natural barriers to gene flow. In our case, we detected both coarse-scale mountain range clustering and finer-scale short distance population differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…AT12 and AT13; Lega et al . ). This may be due to events that occurred during the population's history (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…However, in spite of the narrow distribution, the critical conservation status and the presence of self‐compatibility, A. thalictrifolia maintains a high level of heterozygosity (Lega et al . ). Moreover, it grows at the base of wet cliffs mainly in unvegetated areas, a habitat considered highly stable, not affected by rapid successional dynamics of vegetation and only occasionally disturbed by rock falls.…”
Section: Introductionmentioning
confidence: 97%